2013
DOI: 10.1590/1414-431x20122515
|View full text |Cite
|
Sign up to set email alerts
|

TNNI3K is a novel mediator of myofilament function and phosphorylates cardiac troponin I

Abstract: The phosphorylation of cardiac troponin I (cTnI) plays an important role in the contractile dysfunction associated with heart failure. Human cardiac troponin I-interacting kinase (TNNI3K) is a novel cardiac-specific functional kinase that can bind to cTnI in a yeast two-hybrid screen. The purpose of this study was to investigate whether TNNI3K can phosphorylate cTnI at specific sites and to examine whether the phosphorylation of cTnI caused by TNNI3K can regulate cardiac myofilament contractile function. Co-im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…These data are in contrast with prior work showing that TNNI3K localizes to the sarcomere Z disc 5 and also conflicts with a recent study suggesting that troponin I may indeed be a substrate of TNNI3K. 6 These data do, however, add to a growing literature investigating the relevance of TNNI3K in cardiac function. This cardiac-specific kinase was first identified nearly a decade ago in a yeast2-hybrid screen for proteins that interact with cardiac troponin I.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…These data are in contrast with prior work showing that TNNI3K localizes to the sarcomere Z disc 5 and also conflicts with a recent study suggesting that troponin I may indeed be a substrate of TNNI3K. 6 These data do, however, add to a growing literature investigating the relevance of TNNI3K in cardiac function. This cardiac-specific kinase was first identified nearly a decade ago in a yeast2-hybrid screen for proteins that interact with cardiac troponin I.…”
contrasting
confidence: 99%
“…Phosphorylation of cardiac troponin I is known to affect myofilament sensitivity and cardiac inotropy. 6 Overexpression of TNNI3K has been shown to enhance phosphorylation at serine 43 and threonine 143 and was associated with increased isolated myocyte contractility. 6 In addition, overexpression of TNNI3K is associated with increased sarcomere length and titin isoform switching, which were independent of p38 phosphorylation.…”
Section: Abraham and Marchukmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that TNNI3K could promote concentric hypertrophy with enhancement of cardiac function via regulating the phosphorylation of cTnI [26] and thus contributed to the regulation of cardiac myofilament contraction [27]. Troponin I (TnI) is a known inhibitory unit of the troponin complex associated with the thin filament.…”
Section: Discussionmentioning
confidence: 99%
“…Kinases in this family share characteristic amino acid sequences of both tyrosine and serine/threonine kinases in the catalytic domain [9]. Integrin-linked kinase (ILK), is another member of the mixed-lineage family, which, to a large extent, is similar to the TNNI3K in structure, function, and gene sequences on the chromosome [10].…”
Section: Introductionmentioning
confidence: 99%